Present-day spiritualities : contrasts and overlaps - Hense, Elisabeth, 1957- (Studies in Theology and Religion, 2013)
Many forms of present-day Western spirituality contribute to people's well-being, whereas others have raised criticism. The study of these different forms is, however, complicated by their continuously diverging practices and ideas. By bringing to bear a multidisciplinary approach, the ten specialists of this volume are able to analyze diverse new instances of spirituality, e.g. in religious contexts (Buddhism, Christianity), popular use, organizations and enterprises, (alternative) health service, and works of art. Most contributions also discuss methods and theories. In their editorial chapters, Elisabeth Hense, Frans Jespers and Peter Nissen show the remarkable overlaps in the approaches, definitions and evaluations of the contributions in this volume and provide a theoretical framework. Both the fresh analyses and the theoretical reflections in this volume point the way to new approaches in this field of study. Contributors include: Jerry Biberman, Mark Elliott, Miguel Farias, Johan Goud, Paul Heelas, Elisabeth Hense, Frans Jespers, Hubert Knoblauch, Peter Nissen, Paul van der Velde